Synthesis of armchair graphene nanoribbons from the 10,10′-dibromo-9,9′-bianthracene molecules on Ag(111): the role of organometallic intermediates - K. A. Simonov (Nature Portfolio, 2018)
Abstract We investigate the bottom-up growth of N = 7 armchair graphene nanoribbons (7-AGNRs) from the 10,10′-dibromo-9,9′-bianthracene (DBBA) molecules on Ag(111) with the focus on the role of the organometallic (OM) intermediates. It is demonstrated that DBBA molecules on Ag(111) are partially debrominated at room temperature and lose all bromine atoms at elevated temperatures. Similar to DBBA on Cu(111), debrominated molecules form OM chains on Ag(111). Nevertheless, in contrast with the Cu(111) substrate, formation of polyanthracene chains from OM intermediates via an Ullmann-type reaction is feasible on Ag(111). Cleavage of C–Ag bonds occurs before the thermal threshold for the surface-catalyzed activation of C–H bonds on Ag(111) is reached, while on Cu(111) activation of C–H bonds occurs in parallel with the cleavage of the stronger C–Cu bonds. Consequently, while OM intermediates obstruct the Ullmann reaction between DBBA molecules on the Cu(111) substrate, they are required for the formation of polyanthracene chains on Ag(111). If the Ullmann-type reaction on Ag(111) is inhibited, heating of the OM chains produces nanographenes instead. Heating of the polyanthracene chains produces 7-AGNRs, while heating of nanographenes causes the formation of the disordered structures with the possible admixture of short GNRs.